THE ANALYSIS OF LEARNING STRATEGIES FOR CHARACTER DEVELOPMENT OF STUDENTS DURING COVID-19 PANDEMIC - Hasan Asy'ari Najmuddin; Lenny Aprilianty (Universitas Islam Negeri (UIN) Mataram, 2020)
Nowadays, Indonesia is still experiencing pandemic issues or the Covid-19 virus outbreak. All the learning activities are suspended temporarily. The purpose is to contain the pandemic outbreak spreading and infection can be ceased. The education issues emerge due to conventional (face to face) or offline learning process is suspended. The rise of social and moral distortion occurred shows the need for improvement in early character-building education. The role of an educational institution is very required in improving Nation’s morality through Character Education using a learning strategy adjusted to pandemic conditions. This is qualitative research with a study case in Anak Tangguh Mataram School by interview, thorough discussion, and observation. The analysis result shows that learning strategy is conducted by collaborating online and offline which integrating character values in every lesson material. Another one is by habituation method in the school or at home in instilling and developing student’s character. And synergy must be performed among the school administrator, chaplain, parent, and society in instilling and developing education character in Anak Tangguh Mataram School